Ethics and ethics committees: HIV serosurveillance in Scotland. Issue 1 (March 1992) - Tappin, D M; Cockburn, F
Abstract : Knowledge of the heterosexual spread of HIV is needed to plan future health-care needs. In December 1989 we gained approval and finance for unlinked anonymous testing of neonatal Guthrie card samples in Scotland. Local ethics committee approval was required before testing could start. Twenty ethics committees were approached in the 15 Scottish health board areas. Nineteen of the committees have agreed, representing 99.6 per cent of births in Scotland. Our method of contacting ethics committees is discussed, as are the points raised.